Efficacy of photodynamic therapy in treatment of adult patients with skin cancer - O. V. Kirsanova (Фармакоэкономика, 2019)
Photodynamic therapy (PDT) is a relatively new non-surgical treatment for cancer and precancerous conditions. The present review focused on studies using PDT in the treatment of basal cell and squamous cell carcinoma and skin melanoma. The aim was to obtain evidence on the efficacy of PTD in the treatment of skin cancer in patients over 18 years old. To that end, we screened the PubMed database of medical and biological publications and the Cochrane Library without restricting the depth of search. Materials and methods. We evaluated the data of meta-analyses, results of randomized controlled trials (RCTs), and systematic reviews on RCTs, where the overall survival, survival without relapse, and survival without progression were assessed. Results. We have found one systematic review of 27 studies of different designs, one meta-analysis of 5 RCTs, and also five RCTs (1165 participants in total), where the efficacy and safety of PDT in patients with basal cell and squamous cell carcinoma were directly compared to surgical treatment, cryotherapy, and chemo-radiation therapy. In another systematic review, PDT used for squamous cell carcinoma was compared with electro-dissection, cryotherapy, curettage, microsurgery and chemo-radiation therapy. According to our search criteria, no comparative studies on the efficacy and safety of PDT in patients with melanoma were found. Conclusion. The review underscores the efficacy of PDT in patients with both basal cell and squamous cell carcinoma. However, the use of PDT resulted in a lower 5-year survival and a greater recurrence rate compared to the surgical treatment. PDT can be recommended as an alternative to surgery and other treatments for basal cell and squamous cell carcinoma.